Prevalence and correlates of lifetime suicide attempt in obsessive-compulsive disorder with major depression. (May 2023) - Samuels, Jack; Bienvenu, O. Joseph; Krasnow, Janice; Grados, Marco A.; Cullen, Bernadette A.; Goes, Fernando S.; McLaughlin, Nicole C.; Rasmussen, Steven A.; Fyer, Abby J.; Knowles, James A.; McCracken, James T.; Geller, Dan; et al.
Abstract: Background: Little is known about specific obsessive-compulsive clinical features associated with lifetime history of suicide attempt in individuals with obsessive-compulsive disorder (OCD) and major depression. Methods: The study sample included 515 adults with OCD and a history of major depression. In exploratory analyses, we compared the distributions of demographic characteristics and clinical features in those with and without a history of attempted suicide and used logistic regression to evaluate the association between specific obsessive-compulsive clinical features and lifetime suicide attempt. Results: Sixty-four (12%) of the participants reported a lifetime history of suicide attempt. Those who had attempted suicide were more likely to report having experienced violent or horrific images (52% vs. 30%; p < 0.001). The odds of lifetime suicide attempt were more than twice as great in participants with versus without violent or horrific images (O.R. = 2.46, 95%, CI = 1.45–4.19; p < 0.001), even after adjustment for other risk correlates of attempted suicide, including alcohol dependence, post-traumatic stress disorder, parental conflict, excessive physical discipline, and number of episodes of depression. The association between violent or horrific images and attempted suicide was especially strong in men, 18–29 year olds, those with post-traumatic stress disorder, and those with particular childhood adversities. Conclusions: Violent or horrific images are strongly associated with lifetime suicide attempts in OCD-affected individuals with a history of major depression. Prospective clinical and epidemiological studies are needed to elucidate the basis of this relationship. Highlights: We studied suicide attempt in adults with obsessive compulsive disorder and depression. Suicide attempt was strongly associated with violent/horrific images. This relationship was independent of other risk correlates of suicide. This relationship was especially strong in those with childhood adversities or PTSD.